Promosi Kesehatan pada Ibu dan Balita Dalam Rangka Menurunkan Angka Kematian dan Kesakitan Balita “Balita Sehat, Ibu Senang” - Ziyadatul Chusna (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Healthy and intelligent children certainly cannot be separated from the role of parents in providing good and sufficient and healthy nutritional intake, whether this is done during the mother's pregnancy or when the child is in a golden age in the growth phase of development that supports intelligence. the child's own brain. The low level of hygiene, the high incidence of diarrhea and the availability of latrines in the village of Kendawa became our background for providing health promotion materials for mothers and toddlers in order to reduce infant mortality in Kendawa Village, Jatibarang District, Brebes Regency. The method in the implementation of the mother is carried out by the lecture method, and discussions using leaflets while the output obtained is increased awareness and knowledge of parents about healthy toddlers in Kendawa Village. The output obtained is the existence of health education media about healthy toddlers in Kendawa Village.